2005
DOI: 10.1136/hrt.2003.032128
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in Europe: lessons from the Euro heart survey

Abstract: Objectives: To describe the characteristics, treatment, and outcomes of active infective endocarditis (IE) in Europe. Design: Prospective survey of medical practices in Europe. Setting: 92 centres from 25 countries. Patients: The EHS (Euro heart survey) on valvar heart disease (VHD) enrolled 5001 adult patients between April and July 2001. Of those, 159 had active IE. Results: 118 patients (74%) had native IE and 41 (26%) had prosthetic IE. Mean (SD) age was 57 (16) years. Blood cultures were obtained for 113 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
227
5
70

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(326 citation statements)
references
References 23 publications
24
227
5
70
Order By: Relevance
“…Studies from the West have shown early surgical intervention to be associated with reduced mortality. [20][21][22] More aggressive and early surgical intervention as has been advocated in many reviews may have improved the outcome and this change in clinical practice is perhaps the need of the hour in developing countries. Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from the West have shown early surgical intervention to be associated with reduced mortality. [20][21][22] More aggressive and early surgical intervention as has been advocated in many reviews may have improved the outcome and this change in clinical practice is perhaps the need of the hour in developing countries. Our study has certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of IE started showing features more commonly seen in the developed countries: a higher mean age at presentation and an increase in prosthetic valve endocarditis. [1][2][3] Streptococcal species remain the commonest causative organisms. The increase in age by a decade at presentation of IE is an important positive finding of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] According to data collected in the Euro Heart Survey study, the mean age of patients at IE onset was 56±17 years in Europe, while a study performed in Greece, one of Turkey's neighbor countries, reported a mean age of 54±17 years. [11,12] The mean age of patients at IE onset is as low as 32 years in countries such as Tunisia and India. [13,14] Studies performed in Turkey in different time points reported the mean age at disease onset varying between 45 and 47 years.…”
Section: Discussionmentioning
confidence: 99%
“…La insuficiencia cardíaca, que se presenta en 50 % a 60 % de los pacientes con EI, es la causa más frecuente de indicación quirúrgica (29); usualmente se debe al daño valvular agudo, con la insuficiencia correspondiente; en 29 % de los casos se afecta la válvula aórtica y en 20 %, la mitral (34). Las fístulas o la obstrucción de las cavidades cardíacas por vegetaciones gigantes son causas menos frecuentes de falla cardíaca.…”
Section: Figura 6 Tratamiento De La Eiunclassified